2001
DOI: 10.1002/app.1975
|View full text |Cite
|
Sign up to set email alerts
|

Properties and morphology of poly(ethylene terephthalate) and high‐density polyethylene blends

Abstract: Blends of poly(ethylene terephthalate) (PET) and high-density polyethylene (HDPE) with and without a compatibilizing agent were studied. Both materials are widely used in the soft drink bottle industry. The compatibilizing agent was a copolymer of ethylene and methacrylic acid partially neutralized with zinc (Surlyn). The olefinic segment of Surlyn is compatible with HDPE, whereas the Surlyn carboxylic acid groups is affine with the PET carbonyl groups. The effectiveness of the compatibilizing agent was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 19 publications
1
29
0
1
Order By: Relevance
“…The poor intrinsic mechanical properties of E-GMA could be another possible reason for the reduced tensile and flexural properties [11]. The compatibilizing role of E-GMA for rHDPE/rPET blends can be confirmed by the toughening behaviour, which implies for SB of blends [18]. Figure 6 and Figure 7 illustrate FTIR spectra of raw materials, uncompatibilized and compatibilizedr HDPE/ rPET (75/25 wt/wt) blends with 5 php E-GMA.…”
Section: Effect Of Compatibilizer Concentrations On Tensile and Flexumentioning
confidence: 95%
“…The poor intrinsic mechanical properties of E-GMA could be another possible reason for the reduced tensile and flexural properties [11]. The compatibilizing role of E-GMA for rHDPE/rPET blends can be confirmed by the toughening behaviour, which implies for SB of blends [18]. Figure 6 and Figure 7 illustrate FTIR spectra of raw materials, uncompatibilized and compatibilizedr HDPE/ rPET (75/25 wt/wt) blends with 5 php E-GMA.…”
Section: Effect Of Compatibilizer Concentrations On Tensile and Flexumentioning
confidence: 95%
“…However, most blends remain immiscible after blending attempts and therefore exhibit poor mechanical properties on a macroscopic scale. [1][2][3][4][5] Different methods can be employed for the compatibilization of the blend polymeric phases. Functionalization of the blend components before blending, addition of a copolymer during mixing process, [5][6][7][8] and also compatibilization through in situ reactive melt mixing 9 -14 promotes in most cases the compatibilization of the phases in the mix.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Different methods can be employed for the compatibilization of the blend polymeric phases. Functionalization of the blend components before blending, addition of a copolymer during mixing process, [5][6][7][8] and also compatibilization through in situ reactive melt mixing 9 -14 promotes in most cases the compatibilization of the phases in the mix. Blends of polyethylene and silicone rubber (PDMS) would be of particular interest because of low glass transition temperature (Ϸ Ϫ120°C), low surface energy, high permeability to gases, good thermal UV and flame resistance, and also good biocompatibility of silicone rubber.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, at high PS concentrations the viscosity is dominated by the continuous PS phase and the relationship falls above the linear curve. Previous researchers [27][28][29][30] have suggested that the incompatible interface between immiscible polymer melts will lead to interlayer slip and a reduction in the apparent viscosity of the blend. Such a phenomenon would increase extruder output upon addition of PS, counter to the observed behavior in Figure 8, and would also generate asymmetry of the output curve about the linear relationship, also not observed.…”
Section: Properties Of Melt-drawn Filamentsmentioning
confidence: 99%
“…Abundant literature exists on the formation of dispersed (droplet/matrix) morphologies. [1][2][3][4][5] In recent years, much research has been focused on immiscible polymer blends with co-continuous morphologies. Co-continuity is defined as the morphological state that exists when both immiscible components are fully continuous throughout the blend system.…”
Section: Introductionmentioning
confidence: 99%